2017
DOI: 10.1159/000479932
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effects of Hormone Therapy in Type 2 Idiopathic Macular Telangiectasia

Abstract: Purpose: To investigate the influence of hormone therapy with tamoxifen or estrogens on morphological changes in macular telangiectasia (MacTel) type 2 patients as revealed clinically in multiple imaging modalities. Methods: Patients with a history of tamoxifen or estrogen use were selected from the cohort of the MacTel Study. A race-, age- and best-corrected visual acuity-matched group of MacTel participants not under hormone therapy served as the comparison group. The frequencies of typical features of the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…There is another set of publications with contrasting results on the progression of MacTel in patients with and without history of tamoxifen use. 7,8 Behrens et al 7 supported the theory that concurrent tamoxifen use in a type 2 MacTel patient could accentuate the fovea atrophy while another paper by Wolf-Schnurrbusch et al suggested that simultaneous use of tamoxifen in a type 2 MacTel did not hasten the structural changes on OCT in type 2 MacTel cases. 8…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…There is another set of publications with contrasting results on the progression of MacTel in patients with and without history of tamoxifen use. 7,8 Behrens et al 7 supported the theory that concurrent tamoxifen use in a type 2 MacTel patient could accentuate the fovea atrophy while another paper by Wolf-Schnurrbusch et al suggested that simultaneous use of tamoxifen in a type 2 MacTel did not hasten the structural changes on OCT in type 2 MacTel cases. 8…”
Section: Introductionmentioning
confidence: 97%
“…There is another set of publications with contrasting results on the progression of MacTel in patients with and without history of tamoxifen use. 7,8 Behrens et al 7 supported the theory that concurrent tamoxifen use in a type 2 MacTel patient could accentuate the fovea atrophy while another paper by Wolf-Schnurrbusch et al suggested that simultaneous use of tamoxifen in a type 2 MacTel did not hasten the structural changes on OCT in type 2 MacTel cases. 8 In this retrospective study, we intended to compare the clinical and imaging findings of a subset of patients with and without tamoxifen retinopathy and another subset of patients with type 2 MacTel with and without history of tamoxifen use.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Findings such as intraretinal crystals, RPE abnormality, and foveal hypo-reflective space on optical coherence tomography (OCT), as seen in patients with tamoxifen retinopathy, may also be observed in patients with macular telangiectasia type 2 (MacTel-2), showing similarity of clinical findings between the two diseases [5]. A previous study of 17 cases with medical history of tamoxifen administration reported MacTel-2-like findings [57]. However, the relationship between anti-estrogen drugs and MacTel-2 is poorly understood.…”
Section: Introductionmentioning
confidence: 99%